Juventude imigrante: estigma, conflito e circuito de lazer na cidade de São Paulo - Pires, Bruno Rafael De Matos [UNIFESP] (2020)
This research addresses the integration of young immigrants and children of Bolivian, Peruvian, and Paraguayan immigrants in the leisure spaces of the city of São Paulo. As discussed throughout the analysis, immigrants of these nationalities live daily with the stigmas created by the local society. These stigmas are passed on from parents to children and have been influencing how they build their identity, occupy city spaces for leisure activities, relate to Brazilians and other immigrants, and also how they react to that negative characterization produced by the receiving society. The research avoids the tendency to view immigrants simply as a workforce (Sayad, 1998). The methodologies adopted were field observation in places frequented by young Bolivian, Peruvian, Paraguayan, and other South American immigrants, such as Coimbra street and Kantuta square, conducting semistructured interviews with young immigrants and their families as well as informal conversations, held at different moments with Brazilian and immigrant interlocutors. As a result, it was figured out that Coimbra street is not the only place frequented by immigrant youth, while other spaces are increasing in the metropolitan region of São Paulo. Among them, the night parties located in Vila Maria, Pari, and Centro are standing out, as well as an MC battle which, is known by its organizers as Batalla Callejera.